1992
DOI: 10.1007/bf00443936
|View full text |Cite
|
Sign up to set email alerts
|

Partial suppression of cell mediated immunity in chromoblastomycosis

Abstract: The cellular immune response of 8 patients from the Brazilian Amazon region with chromoblastomycosis was analyzed. Primary immunological responses of patients were tested by contact sensitization to 2,4-dinitro-chlorobenzene (DNCB), or rejection of first set skin allografts. 2 of 8 patients were reactive to DNCB after sensitization, and skin allograft rejection occurred in an average of 14 days. Capacity of patients to mount recall immunological responses was measured by skin testing with two fungal antigens a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…In this context attention may be called to a recent clinical study of eight chromoblastomycosis patients [16]. It was pointed out that a partial suppression of cell-mediated immune response to fungal antigens occurred at some point during the patients' infections and might have played a predisposing role.…”
Section: Discussionmentioning
confidence: 99%
“…In this context attention may be called to a recent clinical study of eight chromoblastomycosis patients [16]. It was pointed out that a partial suppression of cell-mediated immune response to fungal antigens occurred at some point during the patients' infections and might have played a predisposing role.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of CD4 ϩ cells by macrophages responsible for the engulfment of F. pedrosoi is essential to prevent CBM development (228). Impairment of cell-mediated immunity in CBM patients led to an inefficient reaction to fungally derived antigens, resulting in the maintenance of CBM-related fungi in lesional skin (229). A delayed-type hypersensitivity (DTH) reaction in F. pedrosoi CBM indicates that inflammation may be mediated by T cells (227).…”
Section: Adaptive Immune Responsementioning
confidence: 99%
“…It has been demonstrated that cell-mediated immunity in patients with a chronic form of black yeast infection is impaired and that patients are unable to develop an efficient immune reaction to fungal antigens, which corresponds to the chronicity and persistence of the fungus in tissue (113). In experimental infection models using athymic mice infected with black yeasts, it was shown that during the course of infection, granulomas became diffuse and confluent, with a random fungal distribution, suggesting a role for a T-cell-mediated immune response (114).…”
Section: Adaptive Immunitymentioning
confidence: 99%